2004
DOI: 10.1186/1550-2783-1-2-7
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Effects of the Very-Low-Carbohydrate Diets: Misunderstood "Villains" of Human Metabolism

Abstract: During very low carbohydrate intake, the regulated and controlled production of ketone bodies causes a harmless physiological state known as dietary ketosis. Ketone bodies flow from the liver to extra-hepatic tissues (e.g., brain) for use as a fuel; this spares glucose metabolism via a mechanism similar to the sparing of glucose by oxidation of fatty acids as an alternative fuel. In comparison with glucose, the ketone bodies are actually a very good respiratory fuel. Indeed, there is no clear requirement for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 17 publications
1
50
0
1
Order By: Relevance
“…74 For example, misunderstanding about the body's need for glucose, in particular by the central nervous system, continues despite basic scientific knowledge to the contrary. 5 In concert, the ADA does not recommend a low-carbohydrate diet for diabetes management. While recognising that 'carbohydrate intake has a direct effect on postprandial glucose levels' and 'total amount of carbohydrate eaten is the primary predictor of glycaemic response', the ADA advises that 'a variety of eating patterns (combinations of different foods or food groups) are acceptable for the management of diabetes' and recommends adjusting carbohydrate intake to mealtime insulin dosing.…”
Section: Trials Of Low-carbohydrate Diets: Significant Findings For Amentioning
confidence: 99%
See 1 more Smart Citation
“…74 For example, misunderstanding about the body's need for glucose, in particular by the central nervous system, continues despite basic scientific knowledge to the contrary. 5 In concert, the ADA does not recommend a low-carbohydrate diet for diabetes management. While recognising that 'carbohydrate intake has a direct effect on postprandial glucose levels' and 'total amount of carbohydrate eaten is the primary predictor of glycaemic response', the ADA advises that 'a variety of eating patterns (combinations of different foods or food groups) are acceptable for the management of diabetes' and recommends adjusting carbohydrate intake to mealtime insulin dosing.…”
Section: Trials Of Low-carbohydrate Diets: Significant Findings For Amentioning
confidence: 99%
“…4 The CDC's review of 2015 data reported more than 114 million Americans have diabetes or pre-diabetes. 5 While the rate of new diagnoses remains steady, the report noted that 9.4% (30.3 million of the 114 million estimated) of the US population has diabetes -an increase from 29.1 million in 2014. Countries with historically low diabetes rates are also now affected: almost half the population of China has pre-diabetes, and 10% have the diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…It has been debated whether lipid combusts in a flame of carbohydrate (Manninen 2004). Our data suggest that glycolytic pathway plays an important role for the lipid-metabolism to maintain the physiological responses.…”
Section: Discussionmentioning
confidence: 79%
“…Among the five amino acids that exhibited large effects, lysine, phenylalanine, and tyrosine are ketogenic amino acids, which can be converted to fatty acids in starvation-stressed organisms [33], and lysine, threonine, and phenylalanine are essential amino acids, ones that animals must obtain from their diet [34]. By contrast, alanine, proline, and glycine, which exhibited a small effect on growth, are neither ketogenic nor essential amino acids.…”
Section: Discussionmentioning
confidence: 99%